The sharpshooter genus Apogonalia Evans (Hemiptera: Cicadellidae: Cicadellini): description of females and key to species - Felix, Márcio; Mejdalani, Gabriel (Zootaxa, 2017)
The Cicadellinae genus Apogonalia Evans, 1947 currently has 22 species and occurs from Arizona (USA) to Panama and the Antilles. Color pattern and female genital structures of 21 species of Apogonalia are here described and illustrated (the female of A. nielsoni Felix & Mejdalani, 2006 is unknown). Comparative morphological notes are included. The female of A. angusta Freytag, 2004 is described for the first time. A key to males and females of all known species of the genus is provided.